2016
DOI: 10.3389/fpls.2016.01087
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Emergence and Phenotypic Response of Common Bean Germplasm to Different Temperatures under Controlled Conditions and in Open Field

Abstract: Rapid and uniform seed germination and seedling emergence under diverse environmental conditions is a desirable characteristic for crops. Common bean genotypes (Phaseolus vulgaris L.) differ in their low temperature tolerance regarding growth and yield. Cultivars tolerant to low temperature during the germination and emergence stages and carriers of the grain quality standards demanded by consumers are needed for the success of the bean crop. The objectives of this study were (i) to screen the seedling emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…Higher stand densities at maturity were observed in Iowa compared to other locations. This result could be attributable to differences in site management (weed, pest, and disease control) which influenced germination rates and/or edaphic factors on seedling emergence [25,26]. Yields observed in this study were within the range of yields reported by Kandel et al [27] in Canada and Balasubramanian et al [28] in North Dakota.…”
Section: Discussionsupporting
confidence: 64%
“…Higher stand densities at maturity were observed in Iowa compared to other locations. This result could be attributable to differences in site management (weed, pest, and disease control) which influenced germination rates and/or edaphic factors on seedling emergence [25,26]. Yields observed in this study were within the range of yields reported by Kandel et al [27] in Canada and Balasubramanian et al [28] in North Dakota.…”
Section: Discussionsupporting
confidence: 64%
“…Heat stress High temperature (HT) stress is a major bean production constraint (Rainey and Griffiths 2005;De Ron et al 2016). HT (greater than 30°C day and/or greater than 20°C at night) causes significant reduction in yield and quality and limits environmental adaptation.…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…The entries were arranged in a completely randomised block design with three replications. For each entry and in each replication, five plants were assessed [44]. The row plots measured 300 cm in length and were spaced 70 cm apart; plants within row plots were spaced 50 cm apart.…”
Section: Multi-environment Field Trialsmentioning
confidence: 99%